Health Education Against Changes in Physical Activity Patterns and Body Mass Index - Asnidar; Muriyati; Asri; Safruddin; Haerani; Hamdana (Jurnal Penelitian Pendidikan IPA, 2023)
Obesity problems in children will be at high risk of obesity in adulthood and potentially experience various causes of significant risks for some chronic diseases associated with diets, such as type 2 diabetes mellitus, hypertension, stroke, cardiovascular disease, and certain types of cancer.This research aims to determine the effect of health education based on social media to the pattern of physical activity and body mass index (BMI) adolescent overweight and obesity of each group and between groups in Bulukumba, Indonesia. The design of this research is the "Quasi Experiment," which is a pretest and post-test wa ith control group design. The population in this study were overweight and obese adolescents in Bulukumba Regency. The number of samples is 91 people divided into 4 (four) groups. The analysis used is the Friedman test, Kruskal Wallis, repeated ANOVA, and one-way ANOVA. The intervention was given for six months through health education with a lecture media booklet in groups 1 and 2, leaflets in group 3, and lecture method alone without media in group 4. In groups 1 and 2, we were given re-education through the WhatsApp application in group 1 and through messages in group 2. Periodic time series measurements were taken for six months on the variables of physical activity pattern and BMI.Â The results showed an effect of health education on the changing of activity patterns in each and between groups. There is an effect of health education on BMI changes in groups of 1,2 and 3 and between groups, but there is no influence on group 4. This study recommends to health workers (nurses, nutritionists, and health promotion) the use of booklets and utilizing social media (WhatsApp) in providing health education related to obesity.Â